Gestational Exposure to Particulate Matter 2.5 (PM(2.5)) Leads to Spatial Memory Dysfunction and Neurodevelopmental Impairment in Hippocampus of Mice Offspring - Zheng, Xinrui (Front Neurosci, 2019)
Prenatal exposure to air pollutants has long-term impact on growth retardation of nervous system development and is related to central nervous system diseases in children. However, it is not well-characterized whether gestational exposure to air pollutants affects the development of nervous system in offspring. Here, we investigated the effects of gestational exposure to particulate matter 2.5 (PM(2.5)) on hippocampus development in mice offspring, through neurobehavioral, ultrastructural, biochemical and molecular investigations. We found that spatial memory in mice offspring from PM(2.5) high-dosage group was impaired. Next, hippocampal ultrastructure of the mice offspring in puberty exhibited mitochondrial damage related to PM(2.5) exposure. Interestingly, EdU-positive cells in the subgranular zone (SGZ) of offspring from PM(2.5) high-dosage group decreased, with NeuN(+)/EdU(+)cells reduced significantly. Furthermore, the numbers of NeuN(+)/TUNEL(+), GFAP(+)/TUNEL(+), and Iba1(+)/TUNEL(+) double-labeled cells increased with PM(2.5) exposure in a dosage-dependent manner. In addition, gestational exposure to PM(2.5) resulted in increased levels of both mRNAs and proteins involved in apoptosis, including caspase-3, -8, -9, p53, and c-Fos, and decreased Bcl-2/Bax ratios in the hippocampus of mice offspring. Moreover, gestational exposure to PM(2.5) was dosage-dependently associated with the increased secretions of inflammatory proteins, including NF-κB, TNF-α, and IL-1β. Collectively, our results suggest that gestational exposure to PM(2.5) leads to spatial memory dysfunction and neurodevelopmental impairment by exerting effects on apoptotic and neuroinflammatory events, as well as the neurogenesis in hippocampus of mice offspring.